Navashree and Nithyashree - two new high yielding and high quality cinnamon (Cinnamomum verum Bercht & Presl.) selections - ZACHARIAH, JOSE ABRAHAM, A GOPALAM, B KRISHNAMOORTHY, J REMA, T JOHN (Journal of Spices and Aromatic Crops, 1996)
Nine elite cinnamon (Cinnamomum verum) lines were evaluated for their yield and quality during 1990-95 at the Experimental Farm of Indian Institute of Spices Research at Peruvannamuzhi (Kerala State, India). Two lines, namely, SL 63 and In 189 yielding 55.6 kg and 54.2 kg dry barklha per year, respectively, were selected based on their regeneration capacity, yield and quality. These two lines named N avashree and Nithyashree also had higher bark and leaf oil and oleoresin contents and have been recommended for cultivation in all cinnamon growing areas in India.